Visual and Action-control Expressway Associated with Efficient Information Transmission in Elite Athletes. (15th April 2019) - Zhu, Hua; Pi, Yan-Ling; Qiu, Fang-Hui; Wang, Feng-Juan; Liu, Ke; Ni, Zhen; Wu, Yin; Zhang, Jian
Abstract: Effective information transmission for open skill performance requires fine-scale coordination of distributed networks of brain regions linked by white matter tracts. However, how patterns of connectivity in these anatomical pathways may improve global efficiency remains unclear. In this study, we hypothesized that the feeder edges in visual and motor systems have the potential to become "expressways" that increase the efficiency of information communication across brain networks of open skill experts. Thirty elite athletes and thirty novice subjects were recruited to participate in visual tracking and motor imagery tasks. We collected structural imaging data from these subjects, and then resolved structural neural networks using deterministic tractography to identify streamlines connecting cortical and subcortical brain regions of each participant. We observed that superior skill performance in elite athletes was associated with increased information transmission efficiency in feeder edges distributed between orbitofrontal and basal ganglia modules, as well as among temporal, occipital, and limbic system modules. These findings suggest that there is an expressway linking visual and action-control system of skill experts that enables more efficient interactions of peripheral and central information in support of effective performance of an open skill. Highlights: Neural network properties correlated with elite open skill performance. Graph theory analysis reveals "expressways" connecting action-control and visual centers. Increased information transmission efficiency through changes in feeder edges